2021
DOI: 10.1101/2021.07.28.454235
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The timescale and magnitude of 1/f aperiodic activity decrease with cortical depth in humans, macaques, and mice

Abstract: Cortical dynamics obey a 1/f power law, exhibiting an exponential decay of spectral power with increasing frequency. The slope and offset of this 1/f decay reflect the timescale and magnitude of aperiodic neural activity, respectively. These properties are tightly linked to cellular and circuit mechanisms (e.g. excitation:inhibition balance, firing rates) as well as cognitive processes (perception, memory, state). However, the physiology underlying the 1/f power law in cortical dynamics is not well understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Indeed, we find that the correspondence between haemodynamic and electromagnetic connectivity is associated with cytoarchitectural variation across the cortex, such that regions with higher density of granular cells have higher cross-modal correspondence, and vice versa. This is consistent with the notion that neural oscillations and the BOLD response mirror cytoarchitectural organization, as a result of distinct feedforward and feedback projections between different cortical layers and subcortical regions [20,35,51,97]. For example, previous studies of animal electrophysiological recordings demonstrated that visual and frontal cortex gamma activity can be localized to superficial cortical layers (supragranular layers I-III and granular layer IV), whereas alpha and beta activity are localized to deep, infragranular layers (layers V-IV) [8,9,20,72,73,100].…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, we find that the correspondence between haemodynamic and electromagnetic connectivity is associated with cytoarchitectural variation across the cortex, such that regions with higher density of granular cells have higher cross-modal correspondence, and vice versa. This is consistent with the notion that neural oscillations and the BOLD response mirror cytoarchitectural organization, as a result of distinct feedforward and feedback projections between different cortical layers and subcortical regions [20,35,51,97]. For example, previous studies of animal electrophysiological recordings demonstrated that visual and frontal cortex gamma activity can be localized to superficial cortical layers (supragranular layers I-III and granular layer IV), whereas alpha and beta activity are localized to deep, infragranular layers (layers V-IV) [8,9,20,72,73,100].…”
Section: Discussionsupporting
confidence: 89%
“…While this still represents a broad frequency range, and is consistent with other EEG studies utilising spectral parameterisation ( Carter Leno et al, 2021 , Cellier et al, 2021 , Merkin et al, 2021 , Robertson et al, 2019 ), future work could extend these analyses to even wider frequency ranges to capture higher frequency activity (e.g., > 40 Hz). This might be particularly useful for more directly comparing MEG and EEG derived data with results from local field potential and electrocorticography recordings (e.g., Gao et al, 2017 ; Halgren et al, 2021 ). Finally, emerging evidence indicating that the aperiodic exponent might act as a non-invasive measure of E/I balance ( Gao et al, 2017 , Waschke et al, 2021 ) opens exciting possibilities for research into the neurobiology of developmental and neuropsychiatric disorders linked to dysfunction within excitatory and inhibitory circuits, such as autism and schizophrenia ( Foss-Feig et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…While this still represents a broad frequency range, and is consistent with other EEG studies utilising spectral parameterisation (Carter Leno et al, 2021;Cellier et al, 2021;Merkin et al, 2021;Robertson et al, 2019), future work could extend these analyses to even wider frequency ranges to capture higher frequency activity (e.g., > 40 Hz). This might be particularly useful for more directly comparing MEG and EEG derived data with results from local field potential and electrocorticography recordings (e.g., Gao et al, 2017;Halgren et al, 2021). Finally, emerging evidence indicating that the aperiodic exponent might act as a non-invasive measure of E/I balance (Gao et al, 2017;Waschke et al, 2021) opens exciting possibilities for research into the neurobiology of developmental and neuropsychiatric disorders linked to dysfunction within excitatory and inhibitory circuits, such as autism and schizophrenia (Foss-Feig et al, 2017).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%